2022
DOI: 10.1007/s11892-022-01484-x
|View full text |Cite
|
Sign up to set email alerts
|

CGM in the Hospital: Is It Ready for Prime Time?

Abstract: Purpose of Review The use of continuous glucose monitoring (CGM) in the hospital setting is growing with more patients using these devices at home and when admitted to the hospital, especially during the COVID-19 pandemic. Recent Findings Historically, most evidence for CGM use in the inpatient setting was limited to small studies utilizing outdated CGM technology and analyzing accuracy of sensor measurements. Previous studies have shown reduced sensor accuracy during e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
0
22
0
1
Order By: Relevance
“…• • Protocols for frequent nonadjunctive use of CGM: For example, CGM may directly inform adjustments of insulin infusions, although this has been limited to research settings 13,[88][89][90] or in response to the COVID-19 pandemic. 91,92 Protocols typically require periodic POC glucose measures, often at a lesser frequency than otherwise would be performed in clinical practice.…”
Section: Real-time Usementioning
confidence: 99%
See 2 more Smart Citations
“…• • Protocols for frequent nonadjunctive use of CGM: For example, CGM may directly inform adjustments of insulin infusions, although this has been limited to research settings 13,[88][89][90] or in response to the COVID-19 pandemic. 91,92 Protocols typically require periodic POC glucose measures, often at a lesser frequency than otherwise would be performed in clinical practice.…”
Section: Real-time Usementioning
confidence: 99%
“…103 During the COVID-19 pandemic, reports have emerged on the use of protocols combining CGM and POC to guide intravenous insulin therapy; however, the safety of this approach needs further investigation. 92 Similarly, studies including patients with COVID-19 in non-ICU settings have focused on the feasibility of remote CGM use to decrease the burden of diabetes care, but there has been limited data on insulin dosing.…”
Section: Significance Of Using Cgm Data For Insulin Dosing In the Hos...mentioning
confidence: 99%
See 1 more Smart Citation
“…69 Accuracy may be affected with other substances (namely maltose, ascorbic acid, dopamine, mannitol, heparin, hydroxyurea, and salicylic acid) with certain devices. 11,58,70 Challenges and Future Directions Implementation of diabetes technology in hospital presents several challenges. 61 Continuous glucose monitoring devices are currently infrequently encountered in the hospital, therefore, hospital staff are unlikely to be familiar with their operation.…”
Section: Limitations and Accuracymentioning
confidence: 99%
“…To date, only a handful of randomized-controlled trials (RCTs) have evaluated CGM in hospital settings. Recent reviews of studies evaluating CGM in ICU settings 23 and among hospitalized patients with COVID-19 24,25 show preliminary evidence of superior accuracy, detection, and glycemic control relative to POCT. A large multi-center trial examining the accuracy of CGM in non–critical care inpatient settings demonstrated promising findings in a larger, heterogeneous group of hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%